Trauma and media : theories, histories, and images - Meek, Allen, 1961- (Routledge research in cultural and media studies ;, 2009)
This book provides the first comprehensive account of trauma as a critical concept in the study of modern visual media, from Freud to the present day, looking at how the psychoanalytic theory of trauma was adapted by the cultural critics Walter Benjamin, Theodor Adorno, Roland Barthes, Jacques Derrida, and Slavoj Zizek.